Confiscation as an Essential criminal mechanism for countering Transnational Organized Crime - Dzneladze, Levan (Journal of Law, 2024)
The paper addresses one of the challenging issues of modernity. Although many international and domestic tools[1] have been developed in recent decades, including the fight against transnational organized crime, it is becoming increasingly extensive and global. "According to the International Monetary Fund, revenue from drug trafficking and money laundering accounts for six to eight percent of the global economy.[2] Thus, the fight against this phenomenon necessitates a continually updated approach. The increased use of digital technologies in the public and private sectors made criminals inclined to commit crimes causing immeasurably great economic harm to society. The leading driving factor for Transnational Organized Crime is to make the maximum profit in a short time. The effective fight against this complex criminal event is about recovering and confiscating assets acquired through committing crimes.[3] The paper is based on an analysis of doctrine and judicial practice. It also discusses distinct aspects and modern challenges related to the return of criminal assets in the fight against transnational organized crime. The study aims to identify gaps and measures taken to ensure their solution. [1] Tumanishvili G., (Samets. Ed.), Jishkariani B., (Samets. ed.), Shrami E., (Ed.), Influence of European and International Law on Georgian Criminal Procedure, Tb. 2019, 800-801. [2] Shelley, L., Transnational organized crime and seized assets: moral dilemmas concerning the disposition of the fruits of crime, 7 Maastricht J. EUR. & Comp. L.35 (2000), [24.01.2023]. [3] "Crime does not pay", - White paper on best practices in Asset Recovery, 1, <a href="https://www.interior.gob.es/opencms/pdf/archivos-y-documentacion/documentacion-y-publicaciones/publicaciones-descargables/seguridad-ciudadana/White-paper-on-best-practices-in-asset-recovery-NIPO-126-12-071-X.pdf">https://www.interior.gob.es/opencms/pdf/archivos-y-documentacion/documentacion-y-publicaciones/publicaciones-descargables/seguridad-ciudadana/White-paper-on-best-practices-in-asset-recovery-NIPO-126-12-071-X.pdf [05.08.2024].